Control Strategy of Hybrid AC/DC Microgrid in Standalone Mode - Qachchachi, Nabil; Mahmoudi, Hassane; El Hassnaoui, Abdennebi (International Journal of Renewable Energy Development, 2020)
The fluctuation of production of renewable energy resources (RESs) is a big problem for its installation and integration in isolated residential buildings. A hybrid AC/DC microgrid facilitates the good operation of RESs with a storage system in standalone mode and the possibilities of smart energy management. In this paper optimization research of the hybrid ac/dc microgrid in isolated mode of operation is presented. The power system is supplied by various Renewable Energy Resources (RESs), Photovoltaic arrays (PVA), a Wind Turbine Generator (WTG), Diesel Generator (DG) and supported by Batteries Storage System (BSS) for short term storage. The main objective of this study is to optimize power flow within a hybrid ac/dc microgrid with regards to reliability in islanded mode. First a mathematical model optimized by mixed integer linear programming and solved by CPLEX solver with JAVA language is developed for an islanded RES system and then, based on the developed model, the power system control is simulated for different cases of off-grid mode. Simulation results have shown that the management strategy can maintain power balancing while performing optimized control and give a controllable loads and batteries charging/discharging powers, even with unpredictability of RESs powers outputs and arbitrary energy tariffs. Finally, the proposed algorithm respects the optimization in real-time operation under various constraints.%.